2000
DOI: 10.1109/42.876307
|View full text |Cite
|
Sign up to set email alerts
|

Image registration by maximization of combined mutual information and gradient information

Abstract: Mutual information has developed into an accurate measure for rigid and affine monomodality and multimodality image registration. The robustness of the measure is questionable, however. A possible reason for this is the absence of spatial information in the measure. The present paper proposes to include spatial information by combining mutual information with a term based on the image gradient of the images to be registered. The gradient term not only seeks to align locations of high gradient magnitude, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
206
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(210 citation statements)
references
References 11 publications
3
206
0
1
Order By: Relevance
“…Adaptation of mutual information by incorporating spatial information proposed by Pluim et al (2000) (hereafter referred as Pluim), which is the multiplication of the mutual information and a gradient term based on both the magnitude and orientation of image gradient. Second-order mutual information proposed by Rueckert et al (2000) (hereafter referred as Rueckert), which considers the co-occurrence of intensity pairs of adjacent points in each of the images to be registered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptation of mutual information by incorporating spatial information proposed by Pluim et al (2000) (hereafter referred as Pluim), which is the multiplication of the mutual information and a gradient term based on both the magnitude and orientation of image gradient. Second-order mutual information proposed by Rueckert et al (2000) (hereafter referred as Rueckert), which considers the co-occurrence of intensity pairs of adjacent points in each of the images to be registered.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results using clinical three-dimensional CT and T1-weighted MRI image volumes from the retrospective image registration evaluation (RIRE) project (West et al, 1997), it is experimentally shown that, at different image resolutions, the proposed method can give longer capture ranges than the conventional mutual information based method and two of its adaptations (respectively proposed by Pluim et al (2000) and Rueckert et al (2000)) with incorporating spatial information. This can obviously make the multi-resolution image registration more robust.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 14 15 ) However, in addition to the high computational complexity of MI for 3D image, optimization process can always be trapped into local extremes when searching for the global optimum and, hence, result in misalignment. Although multiscale registration methods can improve the registration efficiency including speed, accuracy, and robustness, ( 5 , 16 ) Pluim et al ( 17 ) believed that one reason for misregistration in MI‐based registration is the absence of spatial information in MI measurement.…”
Section: Introductionmentioning
confidence: 99%